Quadrotor UAV: collision resilience behaviors - Fan, Dadong (2023)
In this article, a safety control scheme for quadrotor is proposed to guarantee collision resilience like flying insects. The direction and magnitude of contact wrench are quantitatively analyzed subject to the compliant contact wrench model. A nonlinear disturbance observer is developed to estimate the contact wrench exerted on the quadrotor, and effective collision detection can be guaranteed based on the observer. Subsequently, a tilt-torsion decomposition-based attitude controller is developed to prioritize the correction of horizontal posture over yaw error. The attitude error is separated into roll-pitch portion and yaw portion. Reasonable roll and pitch torques can be generated by allocating a higher gain for roll-pitch portion, allowing the quadrotor to recover from collisions promptly. Simulations and flight experiments are carried out to demonstrate the effectiveness of the proposed collision resilience control scheme.